EFEKTIVITAS PENANGANAN KASUS PORNOMEDIA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Azi Pratas Guspitu (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2022)
The development of the use of communication and information technology has become the main means in matters relating to pornographic cases today, especially with regard to porn media, so that Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions is closely related to Law Number 44 of 2008 concerning Pornography. The purpose of this research are; 1) Analyzing the effectiveness of handling porn media cases from Law Number 44 of 2008 concerning Pornography in relation to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, and 2) Finding obstacles in handling of porn media cases is related to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The specifications of the research were carried out in a descriptive analytical manner, namely describing the applicable regulations related to legal theory, and their implementation regarding the problems studied. Method The approach uses normative juridical research which is research that examines and analyzes legal norms that have been set by the authorized official for that. The norms that become the object of the study include laws and government regulations. The conclusions of this study are 1) The effectiveness of handling porn media cases in terms of Law Number 44 of 2008 concerning Pornography, is still not able to effectively tackle porn media cases in the community, because law enforcers have not been able to see the importance of the law, due to violations immorality related to pornography is still not clearly defined. So that the effectiveness of handling online porn media cases must be related to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. 2) Obstacles in handling online pornographic cases from Law Number 44 of 2008 concerning Pornography are associated with Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, relating to juridical obstacles such as the absence of special legislation on cyber crime, and the authority of investigators to conduct searches on suspicions of using criminal, non-juridical tools, such as limited capabilities and the number of officers who master computer technology and lack of equipment, investigative processes and evidence.